Excellent electromagnetic interference shielding and mechanical properties of high loading carbon-nanotubes/polymer composites designed using melt recirculation equipped twin-screw extruder. (August 2015) - Verma, Pawan; Saini, Parveen; Malik, Rajender Singh; Choudhary, Veena
Abstract: This paper describes for the first time a facile, scalable and commercially viable melt blending approach involving use of twin-screw extruder with melt recirculation provision, for uniform dispersion of up to 4.6 vol% multiwall carbon nanotubes (MWCNTs) within polypropylene random copolymer (PPCP). Morphological characterization of PPCP/MWCNT nanoscale composites (NCs) was done using scanning electron microscopy and transmission electron microscopy, which show good dispersion of MWCNTs in the PPCP matrix even at high loadings and confirm the formation of true NCs. The improved dispersion leads to the formation of electrically conducting three dimensional networks of MWCNTs within PPCP matrix at very low percolation threshold (∼0.19 vol%). The attainment of dc conductivity value of ∼10 −3 S/cm, tensile strength of ∼42 MPa and good thermal stability for 4.6 vol% MWCNTs loading NC along with electromagnetic interference (EMI) shielding effectiveness (SE) value of −47 dB (>99.99% attenuation), demonstrate its potential for making light weight, mechanically strong and thermally stable EMI shields. These NCs also display specific SE value of ∼−51 dB cm 3 /g which is highest among unfoamed polymer NCs.